1998
DOI: 10.1007/s004150050225
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral loss of vestibular function: clinical findings in 53 patients

Abstract: The clinical presentations and aetiologies of a series of 53 cases of bilateral vestibular failure (BVF) seen by the authors over a decade were evaluated by retrospective review of the medical records. Thirty-nine per cent of patients had associated neurological disease; 13% had a progressive cerebellar syndrome with disabling gait ataxia, abnormal eye movements and cerebellar atrophy on neuro-imaging. BVF was usually unsuspected. Nine per cent had cranial or peripheral neuropathies and in this group there was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
125
3
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(143 citation statements)
references
References 40 publications
10
125
3
5
Order By: Relevance
“…They also usually have oscillopsia and/or vertigo, neither of which was present in our patient. 7 Review of the patient's medical records revealed that her anemia was long-standing. She confirmed that she had no history of chemotherapy, radiation therapy, or unusual exposure to chemicals.…”
Section: Which Onementioning
confidence: 99%
“…They also usually have oscillopsia and/or vertigo, neither of which was present in our patient. 7 Review of the patient's medical records revealed that her anemia was long-standing. She confirmed that she had no history of chemotherapy, radiation therapy, or unusual exposure to chemicals.…”
Section: Which Onementioning
confidence: 99%
“…Bilateral vestibular loss causes ataxia and oscillopsia, not vertigo, 27 and in the absence of any significant and relevant hearing loss it can cause diagnostic difficulties because an aural cause might not be considered in the differential diagnosis of imbalance. The patient will be able to walk perfectly well heel to toe and the only easily demonstrable abnormality will be an inability to stand, with the eyes closed, but only when trying to do so on a soft, yielding surface such as a mattress or two pillows -a sort of Romberg's test.…”
Section: Bilateral Vestibulopathymentioning
confidence: 99%
“…However, those with bilateral vestibular deficiency (BVD) due to ototoxic drug exposure, MĂ©nière's disease, meningitis, genetic defects, or other insults to the inner ear often suffer from degraded visual acuity during head movements, in addition to postural instability and chronic disequilibrium (Minor 1998;Rinne et al 1998;Black et al 2001Black et al , 2004Mamoto et al 2002). For these individuals, an implantable neuroelectronic prosthesis that measures three-dimensional (3D) head rotation and stimulates the vestibular nerve accordingly could significantly improve quality of life.…”
Section: Introductionmentioning
confidence: 99%